2006
DOI: 10.1002/eji.200535668
|View full text |Cite
|
Sign up to set email alerts
|

IL‐18 stimulates IL‐13‐mediated IFN‐γ‐sensitive host resistance in vivo

Abstract: IL-4 and IL-13 are up-regulated during in vivo responses to many nematode parasites, but increasing evidence suggests that increases in IL-13 can also occur independently of the IL-4-dominant Th2 response. Blocking B7 after Trichuris muris inoculation inhibits resistance and IL-4 elevations, instead resulting in an IFN-c-dominant response associated with susceptibility. However, blocking IFN-c under these conditions restores IL-13-dependent resistance. In this study, we examined the mechanism of IL-13 upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
1
12
0
1
Order By: Relevance
“…20, 21, and 25), the NK cell population was considered a good candidate to contain the IL-13-producing cells. NK cells can be identified by several markers, including NK1.1 and DX5 antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20, 21, and 25), the NK cell population was considered a good candidate to contain the IL-13-producing cells. NK cells can be identified by several markers, including NK1.1 and DX5 antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…The NK1.1 antibody identifies NK cells in selected mouse strains, such as C57BL, FVB/N, and NZB. 20,21 The DX5 antibody targets the CD49b protein, 26 an α-integrin subunit that makes up half of the α2β1 integrin duplex. The CD49b protein is found in both NK and NKT cells of all mouse strains, including the NK1.1-negative strains (129A, AKR, BALB/c, C3H/He, C57BR, C58, CBA, DBA/1, DBA/2, MRL/lpr, and SJL).…”
Section: Resultsmentioning
confidence: 99%
“…This regulatory role of IL-18 seems to be restricted to IL-4 and IL-13 since there was no dysregulation of other Th2 cytokines studied (data not shown). During intestinal nematode infection IL-18 was demonstrated to work as a direct regulator of Th2 cytokines but not as an IFN-g-inducing cytokine (Helmby et al, 2001;Liu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Trichuris muris is also expelled by mucosal mast cells that are activated by the Th2 response. It has been reported that the beneficial effects of IL-18 on this infection are achieved by up-regulating IL-13 [48], although there are some conflicting reports showing deleterious effects of IL-18 on T. muris infection as a result of suppression of IL-4 and IL-13 (most likely, IFN-␥-inducing effects of IL-18) [49]. Nippostrongylus brasiliensis is expelled primarily by mucus derived from IL-13-activated goblet cells [50].…”
Section: Il-18-involved Th2 Response To Nematode Infectionsmentioning
confidence: 99%